2004
DOI: 10.1103/physreve.69.061705
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of a liquid-crystal anchoring transition

Abstract: We present a study of the effects of confinement on a system of hard Gaussian overlap particles interacting with planar substrates through the hard-needle-wall potential. Using geometrical arguments to calculate the molecular volume absorbed at the substrates, we show that both planar and homeotropic arrangements can be obtained using this model. Monte Carlo simulations are then used to perform a systematic study of the model's behavior as a function of the system density and the hard-needle-wall interaction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 52 publications
3
52
0
Order By: Relevance
“…10,[24][25][26][27][28][29][30][31] We have observed the presence of a residual orientational order in the isotropic phase and a second order nematic-isotropic (strictly paranematic) transition for uniform alignment (UA) and homeotropic strong (HOs) anchorings. We find that LC monomers close to the surfaces are endowed of orientational and positional order both in the nematic and the isotropic phase, hinting at the origin of the so-called "surface memory effect".…”
Section: Discussionmentioning
confidence: 99%
“…10,[24][25][26][27][28][29][30][31] We have observed the presence of a residual orientational order in the isotropic phase and a second order nematic-isotropic (strictly paranematic) transition for uniform alignment (UA) and homeotropic strong (HOs) anchorings. We find that LC monomers close to the surfaces are endowed of orientational and positional order both in the nematic and the isotropic phase, hinting at the origin of the so-called "surface memory effect".…”
Section: Discussionmentioning
confidence: 99%
“…This has been illustrated by a series of computer simulation studies performed over the last decade, which have given direct insight into the relationship between molecular adsorption and liquid crystal anchoring. The most common arrangement found in such studies is planar anchoring; this has been found at flat substrates for hard-particle [17][18][19][20], Gay-Berne [21] and all-atom [22] models (though note that planar alignment of the adsorbed molecules does not always result in planar anchoring [23]). Homeotropic anchoring has been achieved using hard-particle systems employing non-additive wall-particle interactions at perfectly flat walls [11,19,20,24,25] and full interactions at walls with tethered flexible chains [25][26][27] and rigid rods [28].…”
Section: Introductionmentioning
confidence: 99%
“…The most common arrangement found in such studies is planar anchoring; this has been found at flat substrates for hard-particle [17][18][19][20], Gay-Berne [21] and all-atom [22] models (though note that planar alignment of the adsorbed molecules does not always result in planar anchoring [23]). Homeotropic anchoring has been achieved using hard-particle systems employing non-additive wall-particle interactions at perfectly flat walls [11,19,20,24,25] and full interactions at walls with tethered flexible chains [25][26][27] and rigid rods [28]. While homeotropic anchoring has been seen in simulations of Gay-Berne particles confined by smooth substrates [21], and could certainly be forced using the well-depth anisotropy tuning approach employed in [29], the majority of such systems have yielded tilted alignments [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Following the approach taken in our previous studies of liquid crystal anchoring [23,24], the pear-shaped particles do not interact directly with the constraining substrates. Instead, particle-substrate interactions are mediated through objects embedded within the mesogenic particles (see Fig.…”
mentioning
confidence: 99%
“…The simulations were performed at constant nematic number density ρ * = 0.15 and in series of increasing and decreasing k S . From these runs, a homeotropic to planar anchoring transition was identified from the behaviour of Q Su zz (ρ * , k S /k) (see [23] for a definition), the density-profile-weighted average of the order tensor element Q zz (z) in the interfacial regions. These data, shown in Fig.…”
mentioning
confidence: 99%